Bounded category of an exact category (2012)
Pedersen-Weibel introduced the notion of bounded category of an additive category, which gives the non-connective delooping of the additive category under consideration. In this work, a possible candidate for the bounded category of an exact category is constructed which shares many properties of the bounded categories of Pedersen-Weibel.